Endoscopic Dilatation versus Oesophageal Stent in Benign Oesophageal Stricture - Hadyanto Caputra; Iqbal I Awang; Prionggodigdo Nugroho; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2016)
Aim: Oesophageal stricture is one of the causes of dysphagia. It is a condition in which the lumen of oesophagus is narrowed by fibrotic tissue in the oesophageal wall. It is usually caused by inflammation or any other cause that leads to necrotizing of tissue. It is mainly differentiated into benign or malignant. The aim of this article is to answer the clinical question on the effectiveness of oesophageal stenting compared to endoscopic dilatation in patient with benign oesophageal stricture due to ingestion of corrosive substances, who had undergone several endoscopic dilatations.Method: We conducted search of relevant articles using PubMed search engine to answer the clinical question. Keywords being used during the search process were: (